Factors Affecting Brittleness Behavior of Coal-Gangue Ceramsite Lightweight Aggregate Concrete - Wang, Yunsen; Qiu, Jingping; Deng, Wen; Xing, Jun; Liang, Jian (Frontiers in Materials, 2020)
Coal gangue is the solid waste produced during the coal processing, and causes serious environmental problems. Lightweight concrete by making use of the coal-gangue ceramsite as the aggregate has many advantages as the construction material. However, the high brittleness of lightweight aggregate concrete is one of the problems in its application in building infrastructure. In this paper, the variation regularity, influencing factors and reinforcing/toughening method were studied as the reference data for future practical applications of coal-gangue ceramsite lightweight aggregate concrete (CGCLWAC). The results show that the brittleness of CGCLWAC increases with age, but the rate of the increase of brittleness keeps decreasing, and the brittleness is basically stable when the age beyond 28 days. When the sand ratio is above 0.38, the brittleness of CGCLWAC increases with the sand ratio; when the water cement ratio is above 0.32, the brittleness increases with the decrease of the water-cement ratio. Experiments show that when the content of steel fibers is less than 1.5%, the brittleness decreases with the increase of steel fiber content; when the content of steel fibers exceeds a critical value, the toughening effect decreases. From the macro-destructive morphology of the specimens, it is concluded that the incorporation of steel fibers can significantly change the brittleness of CGCLWAC. This study aims to provide reference data for making use of the solid waste of the coal gangue and optimizing the infrastructure application scheme of CGCLWAC.